2013
DOI: 10.4992/jjpsy.84.354
|View full text |Cite
|
Sign up to set email alerts
|

How five-year-old children distribute rewards: Effects of the amount of reward and a crying face

Abstract: Five-year-old children were presented with two scenes in which one character made three stars and the other made nine stars. In one of the scenes, both characters' facial expressions were neutral (neutral face scene), and in the other scene the character who produced three stars had a crying face (crying face scene). Children distributed different numbers of rewards to the two characters: equal to (Middle-N), less than (Small-N), or more than (Large-N) the total number of stars in each scene. Then the children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…In condition Four, most participants distributed candies equally under both All and Partial instructions (both were 87.5%), as shown in Table . The All‐Four result is consistent with Tsutsu (, ), who found that most 5‐year‐old children conduct an Equality allocation when the rewards are limited to four. On the other hand, most participants (71.9%) in the present study conducted an Inequality allocation under the condition All‐Three, when following the All instruction, while the use of Inequality in condition Partial‐Three was reported by 40.7% of the participants.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…In condition Four, most participants distributed candies equally under both All and Partial instructions (both were 87.5%), as shown in Table . The All‐Four result is consistent with Tsutsu (, ), who found that most 5‐year‐old children conduct an Equality allocation when the rewards are limited to four. On the other hand, most participants (71.9%) in the present study conducted an Inequality allocation under the condition All‐Three, when following the All instruction, while the use of Inequality in condition Partial‐Three was reported by 40.7% of the participants.…”
Section: Resultssupporting
confidence: 86%
“…Tsutsu () replicated the effect of the numbers of total rewards, and, furthermore, found that the effect remained even when a tearful facial expression of the lower performance character was encountered. Tsutsu () interpreted these results as being that the small number of total rewards elicits the form of automatic processing earlier proposed by Haidt ().…”
Section: The Purposes Of the Present Studymentioning
confidence: 86%
See 3 more Smart Citations